Environmental Protection in Strategic Instruments of Spatial Policy in Poland - Maciej J. Nowak (Studia Ecologiae et Bioethicae)
Ensuring environmental protection requires the use of various instruments, including spatial policy ones. Appropriate integration of environmental issues in spatial policy is still a major challenge. The aim of this article is to determine the direction of optimal environmental protection in strategic tools of spatial policy. The article indicates optimal expectations for spatial policy instruments, from an environmental perspective. Then, it verifies the extent to which these expectations are, or can be, included in the current system. The research part verifies studies of conditions and directions of the spatial development of voivode cities, in terms of using key elements from an environmental perspective. The analyses and research show that, especially in strategic instruments at the local level, consideration should be given to determining the importance of protected areas in shaping the environment, indicating potential solutions to environmental threats, and the social context of environmental protection. However, attempts at such activities are undertaken, largely, to a very limited extent.